Improving the Quality of Islamic Religious Education Learning through Religious Extracurricular Activities - Hasbar, Hasbar; Misbahullah, Misbahullah; Fawwaz, Ahmad Ghiyats (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To find out the implementation of religious extracurricular activities in improving the quality of the Islamic religious education learning process, to find out the obstacles faced in the implementation of religious extracurricular activities in improving the quality of the Islamic religious education learning process and to find out the efforts or solutions made by instructors in overcoming the obstacles faced in the implementation of religious extracurricular activities. Methodology: This type of research is descriptive research. The approach used in this research is to use a qualitative approach. The approach techniques used in this thesis are the pedagogical approach and the management approach. Main Findings: Implementation of religious extracurricular activities, namely reading and writing the Qur'an, lecture or speech training, dhikr together. Obstacles faced in the implementation of extracurricular activities are that 80% of students are unable to read the Qur'an due to lack of motivation and participation from parents of students, in addition students also have a lack of understanding of religion. The solution taken by the school in overcoming obstacles to the implementation of religious extracurricular activities is that student grades are postponed by Islamic religious teachers until students are able to read the Qur'an, Islamic religious teachers write letters to parents of students, practice lectures or speeches, get students used to praying in congregation at the mosque, participate in dhikr activities together every Friday night at the State Senior High School 2 Palopo Mosque Novelty/Originality of this study: This study has the potential to show that the integration of religious activities outside the classroom can enrich students' learning experiences, strengthen understanding of religious values, and support the formation of holistic Islamic character.